2016
DOI: 10.4314/wsa.v42i1.17
|View full text |Cite
|
Sign up to set email alerts
|

Performance comparison of plant root biofilm, gravel attached biofilm and planktonic microbial populations, in phenol removal within a constructed wetland wastewater treatment system

Abstract: This study was performed in order to understand the relative contribution of a constructed wetland (CW) system's various components to phenol degradation (100 mg•L -1 ) under controlled plant biomass/gravel/ water experimental ratios. This was done by division of a pilot-scale CW system into its components, with or without their associated bacteria: (i) gravel, plant and water; (ii) gravel and water; (iii) water; (iv) gravel; (v) plant; (vi) control (sterile water). The highest phenol biodegradation rate occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
2
1
Order By: Relevance
“…Higher total numbers of bacteria on the gravel surface compared to the root surface were attributed to the high surface area of the gravel, although a comparison of the actual surface area of these two components was difficult to perform. The stark differences between the findings of this study and those of Kurzbaum et al [23] are due to the more concentrated effluent (435 mg/L COD) used by Kurzbaum et al [47].…”
Section: The Partial Contribution Of Planktonic Bacteria and Gravel/r...contrasting
confidence: 90%
See 1 more Smart Citation
“…Higher total numbers of bacteria on the gravel surface compared to the root surface were attributed to the high surface area of the gravel, although a comparison of the actual surface area of these two components was difficult to perform. The stark differences between the findings of this study and those of Kurzbaum et al [23] are due to the more concentrated effluent (435 mg/L COD) used by Kurzbaum et al [47].…”
Section: The Partial Contribution Of Planktonic Bacteria and Gravel/r...contrasting
confidence: 90%
“…When the effluent has a high concentration of organic matter, CW treatment may facilitate biofilm development on any surface, thus the contributions of the plant roots and the gravel bed may be equivalent. After separating CW components among tanks and monitoring phenol degradation, Kurzbaum et al [47] were able to attribute the highest contribution to phenol degradation to the gravel-attached biofilm, while the contributions and rates of phenol degradation of the root-attached biofilm and planktonic bacteria were negligible (see graphical abstract for a schematic illustration of the experimental system). In this case, the numbers of specialized phenol degraders were much higher on the gravel surface.…”
Section: The Partial Contribution Of Planktonic Bacteria and Gravel/r...mentioning
confidence: 99%
“…Kurzbaum et al [71] also found that higher total cultivable bacteria and specific phenol-degrading bacteria in gravel attached biofilm than in free water when studying the different CW components to understand the relative contribution for phenol biodegradation. In addition, we also observed that pH and DO were the main variables connecting with biofilm communities (Table S6).…”
Section: Discussionmentioning
confidence: 99%